Throat irritation associated with e-cigarette use: a case report - Martins, Beatriz Nascimento Figueiredo Lebre; Migliorati , César Augusto; Villa, Alessandro (Journal of Oral Diagnosis, 2025)
Electronic cigarette (e-cigarette) is a device popular among non-smoker young adults. We report a case of a patient with the complaint of acute throat irritation secondary to chronic vaping. A 23-year-old male, without a significant past medical history, presented to the emergency department complaining of sore throat. The patient tested negative for Streptococcus (group A strep) and sexually transmitted infections. Due to persistent throat symptoms, he went to the Oral Medicine and Oral Oncology Clinic, at Miami Cancer Institute. He was an avid e-cigarette user, taking the maximum number of puffs from his device in a single day. The intraoral examination revealed erythema of the posterior oropharyngeal wall. The patient was diagnosed with pharyngitis secondary to vaping and instructed to discontinue the use of e-cigarette until the next visit. At 1-month follow-up the patient reported successfully quitting vaping, and had a complete resolution of the throat symptoms, with resolution of the oropharyngeal erythema. This case illustrates the importance of documenting patients’ vaping habit. This information was essential to better understand the source of the throat irritation in the patient. We encourage dental professionals to document patients' vaping habits, educate them about e-cigarettes and the possible complications associated with the habit.